Analisis Pertumbuhan Laba dengan Ukuran Perusahaan Sebagai Variabel Moderasi pada Perusahaan Pertambangan yang Terdaftar Di Bursa Efek Indonesia - Ardi Maulana Efendi; Yuniningsih Yuniningsih; Ira Wikartika (Universitas Batanghari Jambi, 2022)
This study aims to determine and analyze the effect of liquidity, leverage and activity on profit growth and to see the effect of firm size in moderating the relationship between liquidity, leverage and activity on profit growth. The data analysis method used is multiple regression analysis. The mining sector was chosen as the object of research because the mining sector has an important role in the Indonesian economy. The population in this study took mining companies that are still active on the Indonesia Stock Exchange with a time span of 2016-2020 and obtained as many as 45 companies as the research population. In selecting the research sample, purposive sampling method was used by considering certain criteria and data limitations during the observation period, so that 30 companies were obtained that could be used as research samples. The results of this study prove that leverage has a negative effect on profit growth and activity has a positive effect on profit growth. Meanwhile, Liquidity has no effect on profit growth. In addition, firm size cannot moderate the effect of liquidity, leverage and activity on profit growth.